Commuter Rail Electrifications That Never Were and What They Teach Us. Issue 1 (January 2023) - Allen, John G.; Newmark, Gregory L.
North American commuter railroads have experienced two waves of electrification: 1905–1931, and (including renewal and expansion) since the 1980s. Electrification offers many benefits to railroads and society, but also entails considerable capital costs. Eleven proposed electrifications, both in the early 20th century, when private-sector railroads funded and operated services, and in the modern era with public-sector responsibility for financing infrastructure and operations, were never implemented. This research revisits these unrealized proposals to understand the factors that can derail electrification and, conversely, help planners identify promising projects. These examples are explored in their contemporaneous context and in relation to comparable situations where electrification did occur. Key findings include that necessary, if not sufficient, conditions for electrification, in both the private- and public-sector eras, include operating challenges best addressed through electric traction as well as adequate funding. Today, in the public-sector era, electrification also requires political will, an institutional champion, and control of the lines to be electrified. Environmental concerns have become important factors but have not justified electrifications on their own.